Disparities in breast screening, stage at diagnosis, cancer treatment and the subsequent risk of cancer death: a retrospective, matched cohort of aboriginal and non-aboriginal women with breast cancer - David Banham; David Roder; Dorothy Keefe; Gelareh Farshid; Marion Eckert; Natasha Howard; Karla Canuto; Alex Brown; for the CanDAD Aboriginal Community Reference Group and other CanDAD investigators (BMC, 2019)
Abstract Background Australia's Aboriginal and Torres Strait Islander women have poorer survival and twice the disease burden from breast cancer compared to other Australian women. These disparities are influenced, but not fully explained, by more diagnoses at later stages. Incorporating breast screening, hospital and out of hospital treatment and cancer registry records into a person-linked data system can improve our understanding of breast cancer outcomes. We focussed one such system on a population-based cohort of Aboriginal women in South Australia diagnosed with breast cancer and a matched cohort of non-Aboriginal women with breast cancer. We quantify Aboriginal and non-Aboriginal women's contact with publicly funded screening mammograms; quantify exposure to a selection of cancer treatment modalities; then assess the relationship between screening, treatment and the subsequent risk of breast cancer death. Methods Breast cancers registered among Aboriginal women in South Australia in 1990-2010 (N = 77) were matched with a random selection of non-Aboriginal women by birth and diagnostic year, then linked to screening records, and treatment 2 months before and 13 months after diagnosis. Competing risk regression summarised associations of Aboriginality, breast screening, cancer stage and treatment with risk of breast cancer death. Results Aboriginal women were less likely to have breast screening (OR = 0.37, 95%CIs 0.19-0.73); systemic therapies (OR = 0.49, 95%CIs 0.24-0.97); and, surgical intervention (OR = 0.35, 95%CIs 0.15-0.83). Where surgery occurred, mastectomy was more common among Aboriginal women (OR = 2.58, 1.22-5.46). Each of these factors influenced the risk of cancer death, reported as sub-hazard ratios (SHR). Regional spread disease (SHR = 34.23 95%CIs 6.76-13.40) and distant spread (SHR = 49.67 95%CIs 6.79-363.51) carried more risk than localised disease (Reference SHR = 1). Breast screening reduced the risk (SHR = 0.07 95%CIs 0.01-0.83). So too did receipt of systemic therapy (SHR = 0.06 95%CIs 0.01-0.41) and surgical treatments (SHR = 0.17 95%CIs 0.04-0.74). In the presence of adjustment for these factors, Aboriginality did not further explain the risk of breast cancer death. Conclusion Under-exposure to screening and treatment of Aboriginal women with breast cancers in South Australia contributed to excess cancer deaths. Improved access, utilisation and quality of effective treatments is needed to improve survival after breast cancer diagnosis.